PERBEDAAN KECERDASAN EMOSI PADA MUSISI SEKULER DAN MUSISI GEREJA DI KOTA SALATIGA (PSIKOLOGI KONSELING, 2022)
Emotional intelligence is an ability needed in the daily life to confront various situation and condition, especially for both secular and christian musicians which have demand and pressure in living their life phases. Some researches find that most people who deals with the music direclty, either playing or listening to it, have good emotional intelligence. Yet, it does not certify that all secular and christian musicians have good emotional and vice versa. This research is done to know the emotional intelligence differences between secular musicians and christian musicians in Salatiga. The emotional intelligence is measured using emotional intelligence scale according to Goleman (2003) which is developed by Perwitasari (2015). The sample is collected using purposive sampling technique. The subject of the research consists of 36 secular musicians and 37 christian musicians in Salatiga. The data analysis is done by hypothesis test using Independent Sample T-Test which is processed with the help of SPSS 25.0 version. According to the hypothesis test using Independent Sample T-Test shows that the significance value is p = 0,200 (p > 0.05) which means there is not any emotional intelligence differences between secular musicians and christian musicians in Salatiga.
Keywords: Emotional intelligence; music; musician; secular musician; christian musician